Obesity and periodontitis: A systematic review and updated meta-analysis - Kim, Chang Min; Lee, Soobin; Hwang, Wonjun; Son, Eunjeong; Kim, Tae Woo; Kim, Kihun; Kim, Yun Hak (Frontiers in Endocrinology, 2022)
Background: A previous 2014 meta-analysis reported a positive association between obesity and periodontitis. It was considered necessary to update the recently published papers and to analyse subgroups on important clinical variables that could affect the association between obesity and periodontitis. Therefore, we updated the latest studies and attempted to derive more refined results. Methods: All observational studies were eligible for inclusion. The Newcastle–Ottawa scale was used to qualitatively evaluate the risk of bias. Subgroup analyses were conducted for patients aged 18–34, 35–54, and 55+ years and the countries (European countries, USA, Brazil, Japan, Korea, and other Asian countries). Results: Thirty-seven full-text articles were included. Obesity conferred increased odds of periodontal disease with an odds ratio (1.35, 95% CI: 1.05–1.75). In the subgroup analysis by age, the odds ratio was the highest in the 18–34 years group (2.21, 95% CI: 1.26–3.89). In the subgroup analysis by country, European countries had the highest odds ratio (2.46, 95% CI: 1.11–5.46). Conclusion: Despite the differences in degree, a positive association between obesity and periodontitis was found regardless of country or age. Therefore, medical professionals should try to prevent periodontitis by controlling patient weights, and more studies should be conducted to determine the association between obesity and oral health.